Schistosomiasis and cancer: Experience from a zonal hospital in Tanzania and opportunities for prevention - Lodhia, Jay (J Surg Case Rep, 2020)
Schistosomiasis infection is endemic in many parts of Tanzania. The morbidity due to Schistosomiasis and its association with cancer remains to be of great concern and poses greater challenge that needs to be assessed. Cancer is an increasing public health problem in most sub-Saharan African countries, and yet, cancer control programs and the provision of early detection and treatment services are limited despite this increasing burden. This article aims to discuss case series of patients diagnosed with urinary bladder, prostate and colorectal cancer together with Schistosoma infection. We further highlight the opportunities for combating new Schistosomiasis infection, a potential to reduce its oncological complications particularly in low-resource setting.